2018
DOI: 10.1371/journal.pone.0191705
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation and transcriptome analysis of Streptococcus gallolyticus subsp. gallolyticus in response to lysozyme

Abstract: Streptococcus gallolyticus subsp. gallolyticus is a commensal bacterium of the human gastrointestinal tract, and a pathogen causing infective endocarditis and other biofilm-associated infections via exposed collagen. This study focuses on the characterization of the biofilm formation and collagen adhesion of S. gallolyticus subsp. gallolyticus under different conditions. In this study, it has been observed that the isolate UCN 34 is resistant to 20 mg/ ml lysozyme in BHI medium, whereas the strain BAA-2069 bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…In contrast, SGG considered as commensals and isolated from human feces, pigeons and ruminants including the SGG type strain rarely bound to collagen type I, III and IV (Table 3 ). Similar differences were also observed between SGG from infected vs. SGG from healthy humans featuring high vs. low adhesion, respectively (Grimm et al, 2018 ). SGG NCTC8133 and SGP strain ATCC43144 were only shown to bind collagen type IV whereas SGP DSM15351 T strains displayed no adhesion to collagen type I and IV.…”
Section: Mechanisms and Virulence Factors Responsible For Adhesion Ansupporting
confidence: 60%
See 1 more Smart Citation
“…In contrast, SGG considered as commensals and isolated from human feces, pigeons and ruminants including the SGG type strain rarely bound to collagen type I, III and IV (Table 3 ). Similar differences were also observed between SGG from infected vs. SGG from healthy humans featuring high vs. low adhesion, respectively (Grimm et al, 2018 ). SGG NCTC8133 and SGP strain ATCC43144 were only shown to bind collagen type IV whereas SGP DSM15351 T strains displayed no adhesion to collagen type I and IV.…”
Section: Mechanisms and Virulence Factors Responsible For Adhesion Ansupporting
confidence: 60%
“…Most SGG strains derived from human blood cultures of IE or bacteremia patients, pigeons suffering from streptococcosis ( SGG and SGP ) and SL strains derived from sea otters with IE, but also fecal and dairy SBSEC isolates displayed binding to collagen type IV. In contrast, binding to collagen type I was a feature mostly associated with human blood-derived SGG, SGP, SII and SL isolates and partially also with SGM isolates (Vanrobaeys et al, 2000a ; Sillanpää et al, 2008 ; Vollmer et al, 2010 ; Boleij et al, 2011b ; Counihan et al, 2015 ; Grimm et al, 2018 ). Among a panel of human and food-derived SII and SL as well as dairy SGM , adhesion to collagen type I and IV was particularly present in human blood isolates (Boleij et al, 2011b ; Jans et al, 2016 ).…”
Section: Mechanisms and Virulence Factors Responsible For Adhesion Anmentioning
confidence: 99%
“…Ribose-phosphate pyrophosphokinase ( prs ) is a cytoplasmic enzyme involved in multiple metabolisms-associated pathways including pentose phosphate and the glycolytic pathway. The high abundance of ribose may lead to metabolic change associated with TCA cycle stress and biofilm formation [ 28 , 29 ]. A cytoplasmic enzyme 4′-phosphopantetheinyl transferase belongs to pantothenate and CoA biosynthesis was also upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 treatment of Enterococcus faecalis, Streptococcus thermophilus under heat shock, and lysozyme treatment of Streptococcus gallolyticus subsp. gallolyticus also induced the overexpression of such genes [44][45][46], which indicated that lysozyme treatment was related to the production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%